Habitual food, energy, and water consumption behaviors among adults in the United States: Comparing models of values, norms, and identity. (March 2022) - Floress, Kristin; Shwom, Rachael; Caggiano, Holly; Slattery, Jacob; Cuite, Cara; Schelly, Chelsea; Halvorsen, Kathleen E.; Lytle, William
Abstract: Household consumption of food, energy, and water comprises a significant use of resources in the United States. National level authority-based policy tools and top-down systemic shifts have not been widely adopted, thus near-term changes in consumption are dependent upon the actions of individuals. However, typical policy tools intended to change voluntary behaviors rest on information provision, which has been shown to be largely ineffective in achieving necessary consumption shifts. Drawing from the values-beliefs-norms and values-identity-personal norms theories, we compare three models of values, norms, identities, and behaviors using data from a national survey of United States adults' habitual food, energy, and water-related household consumption behaviors. Validated scales for four values (biospheric, altruistic, egoistic, hedonic), environmental self-identity, and three types of personal norms are explored in three structural equation models to interrogate their relationships with each other and behaviors that cross environmental resource domains. We find evidence to support the values-identity-personal norms model in which biospheric values are positively related to environmental self-identity and personal norms, environmental self-identity is related to personal norms, and personal norms are positively and directly related to food, energy, and water behaviors. While norms have been explored across a number of environmental contexts, environmental self-identity may be an additional means of appealing to individuals to make voluntary shifts in consumption in the absence of larger, more systemic changes.